Pengembangan Video Latihan Gerak Dasar Aquatik - fauzan, lazuardy akbar; Shadiqin, AR; Norita, Tulus Eva; Sari, Riska Melina; Ramiro Rap'i, Rakha Shema Alghahitza; Talita, Nourma Alma (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research is development research. This research design uses the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The sample for this research is prospective aquatik athletes in South Kalimantan. This research uses a simple random sampling technique. The data analysis technique in this research is a quantitative descriptive analysis technique with percentages. The results of this research were that at the small trial stage carried out on 10 people, the results were 82.7% in the very good category. At the large trial stage carried out on 30 people, results were obtained in the very good category. The response of the trainer who assessed the development of the training video as many as 3 people revealed that this video could be used as an alternative initial training by observing the movements carried out before the user gets into the swimming pool. Conclusion this training video is useful for use in the training process, especially for prospective beginner athletes and for people who still need basic mastery of aquatik movements. Keywords: Aquatik, Development, Models, Sports,